2016
DOI: 10.1111/1346-8138.13515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maxacalcitol ointment on skin lesions in patients with psoriasis receiving treatment with adalimumab

Abstract: Adalimumab is a biologic that is very effective for treatment of psoriasis. However, recalcitrant or recurrent lesions sometimes occur during treatment. Maxacalcitol is an active vitamin D3 ointment that is effective in treatment of psoriasis. Topical therapy may be beneficial in treatment of recalcitrant or recurrent lesions during treatment with systemic therapy, but there is little evidence on this topic. We investigated the effect of maxacalcitol on skin lesions during treatment with adalimumab in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…These results are consistent with findings from the Danish DERMBIO registry, which reported that the efficacy of biologics diminishes over time and that this reduced efficacy is responsible for the majority of patient discontinuations [53]. Finally, add-on topical treatment with biologics may also be used to enhance treatment outcomes for patients experiencing secondary loss of efficacy or a seasonal fluctuation/flare/ exacerbation of their disease while receiving a biologic [54].…”
Section: Recommendation 3c: For Responder Patients Experiencing Reduced Efficacy On a Biologic Treatment May Be Optimised By The Additionsupporting
confidence: 87%
“…These results are consistent with findings from the Danish DERMBIO registry, which reported that the efficacy of biologics diminishes over time and that this reduced efficacy is responsible for the majority of patient discontinuations [53]. Finally, add-on topical treatment with biologics may also be used to enhance treatment outcomes for patients experiencing secondary loss of efficacy or a seasonal fluctuation/flare/ exacerbation of their disease while receiving a biologic [54].…”
Section: Recommendation 3c: For Responder Patients Experiencing Reduced Efficacy On a Biologic Treatment May Be Optimised By The Additionsupporting
confidence: 87%
“…However, the frequency of exacerbations was significantly reduced in the combination therapy group. 14 We present the findings of a 2-phase, single-center, openlabel observational study of the efficacy and safety of, as well as patient satisfaction with, desoximetasone topical spray 0.25% (Topicort Spray 0.25%; Taro Pharmaceuticals, Inc, Hawthorne, New York) in combination with biologic agents for the treatment of moderate to severe plaque psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the frequency of exacerbations was significantly reduced in the combination therapy group. 14…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated TNF‐ α /IL‐23/IL‐17 axis coincides with the characteristic histopathology of psoriasis, such as epidermal hyperproliferation, aberrant differentiation and neutrophilic microabscess. Regarding treatments, topical application of steroids and vitamin D3 analogues inhibits psoriatic inflammation and normalizes epidermal differentiation . Systemic treatments, such as cyclosporine, methotrexate and the phosphodiesterase 4 inhibitor apremilast, are useful for patients with extensive lesions .…”
Section: Current Pathogenesis Of Psoriasis and Its Treatmentsmentioning
confidence: 99%
“…Regarding treatments, topical application of steroids and vitamin D3 analogues inhibits psoriatic inflammation and normalizes epidermal differentiation. [61][62][63][64][65] Systemic treatments, such as cyclosporine, methotrexate and the phosphodiesterase 4 inhibitor apremilast, are useful for patients with extensive lesions. [66][67][68] Clinical trials have demonstrated the efficacy of the oral janus kinase inhibitor tofacitinib for psoriasis.…”
Section: Current Pathogenesis Of Psoriasis and Its Treatmentsmentioning
confidence: 99%